DEVELOPMENT OF A SYSTEM FOR REGULATING THE THERMAL PROFILE OF ROLLS AND STRIPS DURING HOT ROLLING IN THE FINISHING GROUP OF STANDS - Sanjarbek X. Rayimkulov; Kamoliddin A. Khasanov; Sadulla S. Fayzullayev (Journal of Geography, Regional Planning and Development, 2024)
Thermal regulation is based on the ability of metals to change their -geometric dimensions and volume when temperature changes. This type of regulation can be either external or internal and is carried out in relation to the working tool or the material being processed. The type of control under consideration is inertial and can be used for the ¬finishing group of the mill. The advantage of this method is the ability to influence ¬asymmetrical flatness defects during the rolling process. The use of forced cooling systems for rolled strips, which include interstand cooling (ISC) in the finishing group of stands and accelerated cooling on the outgoing roller table, can increase the productivity of mills and improve the consumer properties of hot-rolled strips.